2020
DOI: 10.1007/s10995-020-02968-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a Home Visiting Program Enhanced with Content on Healthy Birth Spacing

Abstract: Objectives This study sought to determine the impact of Healthy Families Healthy Futures (HFHF) enhanced with Steps to Success (STS). HFHF is a structured home visiting program for teen parents in Houston that focuses on improving parenting skills and preventing child abuse. HFHF enhanced with STS includes content and activities aimed to reduce repeat pregnancies within 24 months after the first child’s birth. Methods The study team … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The systematic review found that some programs increased contraceptive use, with some effects sustained more than 9 months after the program ended. These results are supported by findings from a well-conducted randomized controlled trial of Healthy Families Healthy Futures enhanced with Steps to Success, a home visiting program for teen parents, which found suggestive evidence of increases in use of long-acting reversible contraceptives among the treatment group (Zief et al 2020b , this issue). Finally, consistent with other research (Corcoran and Pillai 2007 ), the systematic review found programs reduced repeat pregnancies or births, particularly rapid repeat pregnancies or births that occurred within 24 months of prior births (Harding et al 2020 , this issue).…”
Section: Programs Can Improve Outcomes For Teen Parentsmentioning
confidence: 53%
See 4 more Smart Citations
“…The systematic review found that some programs increased contraceptive use, with some effects sustained more than 9 months after the program ended. These results are supported by findings from a well-conducted randomized controlled trial of Healthy Families Healthy Futures enhanced with Steps to Success, a home visiting program for teen parents, which found suggestive evidence of increases in use of long-acting reversible contraceptives among the treatment group (Zief et al 2020b , this issue). Finally, consistent with other research (Corcoran and Pillai 2007 ), the systematic review found programs reduced repeat pregnancies or births, particularly rapid repeat pregnancies or births that occurred within 24 months of prior births (Harding et al 2020 , this issue).…”
Section: Programs Can Improve Outcomes For Teen Parentsmentioning
confidence: 53%
“…This supplement makes important contributions to both research and practice related to serving teen parents. Two impact studies, one of which was a replication study, and a systematic review, which included other recent studies funded by the U.S. Department of Health and Human Services in addition to a broader range of studies, illustrate that there are effective programs for promoting positive outcomes for teen parents (Zief et al 2020a , b , this issue; Harding et al 2020 , this issue). Researchers observed impacts on key aspects of teen parents’ self-sufficiency: educational progress, use of contraception, and reductions in repeat pregnancies or births.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations